Predicting bioaccessibility of contaminants of emerging concern in marine sediments using chemical methods - dos Santos, Dayana M. [UNESP]; Williams, Mike; Kookana, Rai; de Marchi, Mary Rosa R. [UNESP] (Springer Nature, 2018)
Purpose: A comparison was made between three chemical methods to predict bioaccessibility of triclosan (TCS), bisphenol A (BPA), and 17α-ethynylestradiol (EE2) in marine sediments, involving an exchangeable (E) value, butanol extractions, and hydroxypropyl-β-cyclodextrin (β-HPCD) extractions. Materials and methods: A 60-day batch experiment was undertaken where the aqueous phase was analyzed by GC-MS/MS. The bioaccessibility study based on the E value model involved monitoring stable isotopes exchanging with the bioaccessible phase, while this exchangeability was also estimated with sediment extractions with butanol and β-HPCD, respectively. Results and discussion: Based on the E value method, TCS was readily exchangeable for up to 7 days, while after this period become virtually non-exchangeable (not detected in aqueous phase). This trend was also evident for butanol and β-HPCD extractions, suggesting TCS was strongly complexed with the matrix. For BPA and EE2, the fraction considered exchangeable was higher after 14 days and the extraction efficiency was slightly higher for the butanol treatment. Conclusions: Chemical methods to predict bioaccessibility in marine sediments have demonstrated differences between selected contaminants, but agreement between methods. Triclosan shows the highest affinity with tested sediments, some exchangeability in the first days of interaction of E value experiment as well as observed for extraction methods. However, the highest capacity to be extracted from already-sorbed phase was observed for BPA, showed in both extraction methods, and confirming its mobility and bioaccessibility in sediments over the time.
Keywords: Emerging contaminant; Isotopic exchangeability; Sediment; Sorption bioaccessible